2020
DOI: 10.1186/s12876-020-01435-4
|View full text |Cite
|
Sign up to set email alerts
|

The association between inflammatory potential of diet and disease activity: results from a cross-sectional study in patients with inflammatory bowel disease

Abstract: Background Diet may play a role in disease status in patients with inflammatory bowel disease. We tested whether the inflammatory potential of diet, based on a summation of pro- and anti-inflammatory nutrients, is associated with disease activity in patients with Crohn’s disease and ulcerative colitis. Methods Participants completed a disease activity questionnaire (short Crohn’s Disease Activity (sCDAI) or Patient Simple Clinical Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 33 publications
4
17
0
1
Order By: Relevance
“…This study consisted of an online survey and interviews. The online survey was part of a larger survey about lifestyle factors and disease activity [ 13 ], which was conducted between July and October 2018. The survey was composed of questions regarding disease activity, physical activity and participants’ characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study consisted of an online survey and interviews. The online survey was part of a larger survey about lifestyle factors and disease activity [ 13 ], which was conducted between July and October 2018. The survey was composed of questions regarding disease activity, physical activity and participants’ characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…IBD patients aged 18 years or older, diagnosed with either CD or UC, were included. Details about recruitment can be found elsewhere [ 13 ]. In total, 397 patients showed interest in the study and received access to our online survey.…”
Section: Methodsmentioning
confidence: 99%
“…Dietary inflammatory index (DII) is an index to quantify the potential inflammatory effect in the diet, which reflects a large literature and population base, and is associated with international standard (238,239). A recent analysis found that dietary patterns with a high DII could increase the risk of CD (240). It has been shown that DII is positively correlated with disease activity in CD patients and there is no correlation between DII and disease activity of UC (241).…”
Section: Educationmentioning
confidence: 99%
“…CD patients may have stronger hedonic desires for food and emotional eating patterns possibly to alleviate symptoms of low mood, anxiety, and depression [ 11 ]. A recent study found an association between the inflammatory potential of diet, as assessed by Dietary Inflammatory Index (DII) [ 19 ] and disease severity in CD but not in UC [ 20 ]. Palatable but, pro-inflammatory foods found in the Western diet may provide immediate reward but worsen CD severity in the long term.…”
Section: Eating Behavior In Ibdmentioning
confidence: 99%